Urban mobility and the smartphone : transportation, travel behavior and public policy - Aguilera, Anne; Boutueil, Virginie (Elsevier, 2019)
Urban Mobility and the Smartphone: Transportation, Travel Behavior and Public Policy provides a global synthesis of the transformation of urban mobility by the smartphone, clarifying the definitions of new concepts and objects in mobility studies, accounting for the changes in transportation and travel behavior triggered by the spread of the smartphone, and discussing the implications of these changes for policy-making and research. Urban mobility is approached here as a system of actors: the perspectives of individual behavior (including lifestyles), the supply of mobility services (including actors, business models), and public policy-making are considered. The book is based on an extensive review of the academic literature as well as systematic observation of the development of smartphone-based mobility services around the world. In addition, case studies provide practical illustrations of the ongoing transformation of mobility services influenced by the dissemination of smartphones. The book not only consolidates existing research, but also picks up on weak signals that help researchers and practitioners anticipate future changes in urban mobility systems. Key Features . Synthesizes existing research into one reference, providing researchers and policy-makers with a clear and complete understanding of the changes triggered by the spread of the smartphone. . Analyzes numerous case studies throughout developed and developing countries providing practical illustrations of the influence of the smartphone on travel behavior, transportation systems, and policy-making. . Provides insights for researchers and practitioners looking to engage with the "smart cities" and "smart mobility" discourse